Fauna of Stigmaeidae and Cryptognathidae (Acari: Trombidiformes) of Lorestan province, with two new records for Iran fauna - Mojtaba Rahmati; katayoon Kheradmand; Sadegh Jafari; Mohammad Bagheri (Journal of Crop Protection, 2015)
A faunestic study on Stigmaeidae and Cryptognathidae families in Lorestan province was carried out during 2012-2013. In this study 18 species were collected and identified, of which Favognathus amygdalus and F. cordylus (Cryptognathidae) were new records for Iranian fauna, also all of the collected species in this study were new records for fauna of Lorestan province. Stigmaeidae with 14 species and Cryptognatidae with four species had the highest and lowest number of identified species, respectively.